Isolation and molecular characterization of probiotic from Sidamanik green tea (Camellia sinensis) fermentation - ALIYAH FAHMI; SUMARYATI SYUKUR; ZULKARNAIN CHAIDIR; SRI MELIA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fahmi A, Syukur S, Chaidir Z, Melia S. 2023. Isolation and molecular characterization of probiotic from Sidamanik green tea (Camellia sinensis) fermentation. Biodiversitas 24: 4277-4288. The bioavailability of green tea catechins is reduced in the gastrointestinal tract because of its instability. Probiotics are expected to increase their bioavailability in the gastrointestinal tract.There is no any information about Sidamanik fermented green tea, either probiotics, antimicrobial activity, or probiotic species that are beneficial to health. This research aims to isolate and test the characterization of probiotics from fermented green tea. Green tea from Sidamanik Sub-district was fermented with palm sugar and forest honey with 24, 48, and 72 h variation times. The fermented green tea was tested for morphological characterization,Gram staining, catalase test, and fermentation test. Then the resistance test to bile acids and salts and the antimicrobial activitytest against three pathogenic bacteria Escherichia coli Q157:H7, Staphylococcus aureus ATCC25923, and Listeria monocytogenes CFSAN004330. Two strains were selected from this series of tests, which were identified using 16S rRNA gene sequencing from different green tea fermented at the same fermentation time. The results indicated a positive lactic acid bacteria (LAB) morphological test. The characteristics of LAB can be described as a single colony being seen with a round, smooth, yellowish-white color, and a clear zone was formed around the colony, positive Gram, negative catalase, and homofermentative. LAB strains 1.1., and 4.1 were chosen to test their antimicrobial activity because they had the best acid and salt resistance viability. Then the results of molecular identification of 16S rRNA gene found that the probiotics contained in LAB strain 1.1. was Lactobacillus plantarum Y-1 and in LAB strain 4.1 was Lacticaseibacillus paracasei HBUAS62903. This study aims to find a new product of fermented green tea that has benefits in digestive health because it contains naturally processed lactic acid bacteria, is cheaper, simpler, stable at room temperature, durable in storage, and easy to serve.